La divulgazione del paesaggio in ambito turistico: criteri, metodi, esperienze - Bradley, Frederick (Ri-Vista. Research for landscape architecture, 2015)
In the tourist context, the landscape meaning, as defined by the European Landscape Convention (ELC), is not yet well understood: actually, landscape is just conceived as a scenic view of the territory (panorama). This situation limits the role that landcape observation should play in policies aimed at promoting a sustainable and competitive tourism development. In order that landscape become a crucial element in visiting and knowing the territory, it is necessary to activate popularization methods able to capture and stimulate the tourist interests. The adoption of polularization methods could make tourism an extraorinary opportunity for applying the ELC principles, as they contitute important tools also for landscape sensitization.